SWOT Strategy To Determine The Strategic Position Of The Islamic Religious College (STAI) Lubuklinggau, South Sumatera Indonesia - Riwukore, Jefirstson Richset; Susanto, Yohanes; Winarni, Indah; Habaora, Fellayanus (International Journal of Educational Research & Social Sciences, 2021)
This research aims to analyze the current strategic position of STAI in Kota Lubuklinggau, South Sumatra, Indonesia, and its development in the future. This research methodology uses a SWOT analysis of the total population and a sample of 13 respondents who come from the leadership elements of STAI. The results showed that STAI was an Islamic Religious College founded by the local government of Kota Lubuklinggau and Musirawas Regency, and the initiative of Lubuklinggau and Regency figures at that time. During the 26 years of existence, many changes have been seen based on data described in the external environment and the internal environment. The current strategic position of STAI is in the quadrant (IA), which is a stabilization growth strategy, which means that STAI can only grow according to its capabilities, even though business opportunities are still available. In other words, STAI growth cannot be drastic (fast), but rather gradual. So there is almost certainly a relatively greater chance of being exploited by competitors. Therefore, STAI must maximize its current strengths by identifying and then using it to seize opportunities by improving building facilities and infrastructure and public facilities and the quality of available lecturers so that they are not taken by other universities in Lubuklinggau City.